A study on issues relating to 'saviour child' law with reference to the law in United Kingdom / Farah Yasmin Abd. Radzak and Mohd. Norsadiq Mohd Yusof - Abd. Radzak, Farah Yasmin; Mohd Yusof, Mohd. Norsadiq (2012)
This research embarks on a study looking at the issues relating to saviour child with reference to the law in UK. Saviour child law had been enacted and accepted by the Supreme Court of UK in an interesting case of Quintavalle v Human Fertilisation and Embryology Authority (HFEA). Although cases of saviour child is still not yet reported or recorded in Malaysia, this research attempts to provide insights into the precautionary steps that we should take towards the issue as saviour child issue in the UK and other European countries is not novel and it is not impossible that one day Malaysia will face this problem because of the rapid growth in reproduction technology. Apart from looking at the moral and ethical issues arising from the creation of savior child, this research will also look at the comparison study between Malaysia and UK and provide the guidelines for future use. This research will be conducted in a qualitative method with library-based materials, and online searching. Hence, this study will be limited to a study on the issues relating to savior child law and not an exact legal comparison on the law in UK and Malaysia. This is because there are no laws that govern the specific matter of savior child in Malaysia.